Kesenjangan Angka Partisipasi Pemilih: PILKADA Riau 2018 dengan PEMILU 2019 di Riau - Hasanuddin Hasanuddin; Annas Rizaldi; Auradian Marta; Ishak Ishak (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
This study aims to explain the condition of the gap in voter participation rates between the 2018 Riau Pilkada and the 2019 Election in Riau. In the 2018 Riau Province Pilkada, voter participation rates were relatively low. In contrast to the election in Riau in 2019, voter participation was relatively high and significantly different. The question is what are the factors that cause the gap in the voter turnout rate? The question becomes interesting, because in fact these two different election momentum were followed by the majority of the same voters, took place in a relatively short time interval and were held in the same place. There are many theoretical options to explain the condition of the existing gap but considering that the two elections were conducted in close proximity, so it is irrational to assume that there is a big change in the condition of voters, this study looks at the difference in stimulus factors that causes the gap as theorized by Milbrath. The method approach in this study uses a mix-method with an emphasis on qualitative methods. While the typology of research applied is causal comparative research. This study found three main factors that caused the gap in voter participation rates in the two election momentums, namely: First, the difference in the number of political actors with an interest in providing stimulus to voters; Second, political echoes that stimulate voters to identify certain candidates who are contesting and are motivated to win them; third, the influence of mass media and social media. This study suggests that the Pilkada be held simultaneously with the regional legislative elections while the presidential elections are carried out simultaneously with the national elections to balance voter participation.